A LOOK AT THE HISTORY OF BUILDING SCHOOLS IN UZBEKISTAN (50-70 YEARS OF THE 20TH CENTURY) (World Bulletin of Social Sciences, 2023)
This article discusses the history of reforms, changes in the system of public education. It is known that after the Second World War, many reforms were carried out in order to raise the educational system. Including a number of works to increase the number of schools in order to improve the quality level of Education. But as a result of the imbalance of schools under construction in the number of students, the fact that education in schools was carried out in two shifts caused a decrease in the quality of Education. Below, an attempt was made to illuminate information about the shortcomings and problems of the construction of school buildings with the help of periodical, archival sources
Keywords: Republic; School; student; Sovkhoz and collective farms